2020
DOI: 10.1016/j.jddst.2019.101459
|View full text |Cite
|
Sign up to set email alerts
|

Manufacturing strategies to develop amorphous solid dispersions: An overview

Abstract: Since the past several decades, poor water solubility of existing and new drugs in the pipeline have remained a challenging issue for the pharmaceutical industry. Literature describes several approaches to improve the overall solubility, dissolution rate, and bioavailability of drugs with poor water solubility. Moreover, the development of amorphous solid dispersion (SD) using suitable polymers and methods have gained considerable importance in the recent past. In the present review, we attempt to discuss the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(31 citation statements)
references
References 117 publications
(138 reference statements)
0
30
0
1
Order By: Relevance
“…This proves that 3DP can be a highly valuable technology for producing personalised pharmaceutical dosage forms to improve physical and sensory properties necessary for a large variety of medicines. The combination of HME and 3DP techniques could be useful to overcome challenges in the formulation development of BCS class II drugs with low solubility, which represent more than 70% of new drug candidates in the pipeline [ 62 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This proves that 3DP can be a highly valuable technology for producing personalised pharmaceutical dosage forms to improve physical and sensory properties necessary for a large variety of medicines. The combination of HME and 3DP techniques could be useful to overcome challenges in the formulation development of BCS class II drugs with low solubility, which represent more than 70% of new drug candidates in the pipeline [ 62 ].…”
Section: Resultsmentioning
confidence: 99%
“…This proves that 3DP can be a highly valuable technology for producing personalised pharmaceutical dosage forms to improve physical and sensory properties necessary for a large variety of medicines. The combination of HME and 3DP techniques could be useful to overcome challenges in the formulation development of BCS class II drugs with low solubility, which represent more than 70% of new drug candidates in the pipeline [62]. It is known from the drug-polymer composition-temperature previously determined by the authors (data not shown) that, at room temperature, 35 wt% PZQ in KOL corresponds to a supersaturated amorphous binary system.…”
Section: Dissolution Profilesmentioning
confidence: 99%
“…The fluid bed coating was recently introduced as an effective technique that involves loading the drug/ carrier mixture on inactive pellets evaporated by flowing air. 78,79 This method can be industrially employed since it is readily flowable for encapsulation and tableting.…”
Section: Solvent Evaporation Methodsmentioning
confidence: 99%
“…The preparation of solid dispersions has been achieved by various methods such as evaporation of a solution, ball milling, spray drying of a solution and hot-melt extrusion (HME) [ 17 , 26 ]. Since environmental concerns have increased recently, HME may be employed more frequently as a solvent-free manufacturing process [ 27 ].…”
Section: Introductionmentioning
confidence: 99%